2014
DOI: 10.2807/1560-7917.es2014.19.12.20745
|View full text |Cite
|
Sign up to set email alerts
|

Atypical hand, foot, and mouth disease associated with coxsackievirus A6 infection, Edinburgh, United Kingdom, January to February 2014

Abstract: In January to February 2014, 16 hand, foot and mouth disease (HFMD) cases were identified in Edinburgh, United Kingdom. All presented with atypical features, with most (n=13) resembling eczema herpeticum or chickenpox. Coxsackievirus A6 (CV-A6) was identified in all the typed cases (n=11). As atypical forms of HFMD associated with CV-A6 are likely to emerge throughout Europe, clinicians should be alert to unusual clinical presentations of HFMD and virologists aware of effective diagnostic testing and enterovir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
63
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 19 publications
6
63
0
5
Order By: Relevance
“…However, since the CV-A16-related outbreak of HFMD occurred in England in 1994 (3), accumulating evidence has demonstrated that CV-A16 infection can also cause severe neurological complications (4) and death (5,6). Recently, CV-A6 infection has also been increasingly associated with HFMD outbreaks around the world (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Furthermore, EV-D68 has been linked to severe respiratory disease worldwide in recent years.…”
mentioning
confidence: 99%
“…However, since the CV-A16-related outbreak of HFMD occurred in England in 1994 (3), accumulating evidence has demonstrated that CV-A16 infection can also cause severe neurological complications (4) and death (5,6). Recently, CV-A6 infection has also been increasingly associated with HFMD outbreaks around the world (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Furthermore, EV-D68 has been linked to severe respiratory disease worldwide in recent years.…”
mentioning
confidence: 99%
“…Esta distribución extensa de las lesiones se asocia a un serotipo CA6 y a factores de riesgo como edad menor de 3 años y dermatitis atópica (2,13) . Dichas presentaciones se conocen como las formas atípicas de EMPB, y difieren en que afectan el área perioral, extremidades y torso, adicional a las manifestaciones clásicas del EMPB, con un exantema eritematoso papular que ocupan más del 10% de superficie corporal total (SCT), y menor compromiso oral (4,14) . Cuatro morfologías distintas caracterizan este exantema atípico (4) : a).…”
Section: Discussionunclassified
“…En sık etken coxsackievirus A16 olup, diğer enterovirüsler ile de hastalık oluşabilmektedir (1)(2)(3)(4)(5) . En sık görülen klinik bulgular; ateş, avuç içi ve ayak tabanlarında küçük veziküller ve oral mukoza ve dilde aftöz lezyonlardır.…”
Section: Discussionunclassified
“…Bu durum, hastane personelinin döküntülü hastaya yaklaşımında koruyucu önlemlerin önemini göstermektedir. Sıklıkla coxsackievirus A6'nın neden olduğu bir atipik el-ayak-ağız hastalığı formu 2008 yılında Asya ve Avrupa'da, 2011 yılında ise Amerika'da tanımlan-mıştır (2,3,5,6) . Bu formda klasik forma göre cilt lezyonları daha belirgin olup, vezikülöbüllöz lezyonlar sık-lıkla el ve ayak dorsal kesimlerinde, gövde ve boyunda daha belirgindir.…”
Section: Discussionunclassified
See 1 more Smart Citation